CONSUMER ACCEPTANCE ON CRACKERS FORTIFIED WITH SHRIMP SKIN EXTRACT - Anita Roza; Dewita Buchari; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aims to determine the level of consumer acceptance of crackers fortified with shrimp skin extracts, as well as the best nutritional value. The treatments were given consisted of K0 (without fortification of shrimp skin extract) K1 (150 g fortification of shrimp skin extract) and K2 (200 g fortification of shrimp skin extract). The analysis parameters observed were consumer acceptance (color, aroma, taste and texture), chemical value (water, ash, protein and crude fibercontent). Fortification of shrimp extract 200 g (K2) produced the best crackers as many as 70 panelists (87.5%) with characteristics of brownish color (3.26), shrimp's aroma was getting stronger (2.55), shrimp taste increasingly felt (3.14), and texture was getting crisper (3.02), with water, ash, protein, and crude fiber content was 10.05%, 5.43%,30.07%, and 31.30%, respectively.Keywords: crackers, shrimp skin extracts, consumer acceptance.